KAJIAN TERHADAP IZIN ANGKRINGAN DI INHIL BERDASARKAN SK BUPATI INHIL DITINJAU DARI FILSAFAT HUKUM ISLAM - Dina Gustina; Raudatul Mardiyah; Saskia Okta Rosellia; Aully Maulaya; Muannif Ridwan (Universitas Islam Indragiri, 2026)
Angkringan, traditional food stalls, are undergoing social change in Indragiri Hilir (Inhil) province, particularly among Generation Z. Through viral spread on social media, angkringan have become a means of expression and a lifestyle element for young people. However, their presence in public spaces, such as sidewalks and streets, raises legal questions and public order issues. This study examines the enforcement of angkringan laws in inappropriate locations and analyzes this phenomenon from the perspective of Islamic legal philosophy. The research is based on an empirical approach involving interviews and field observations. The findings indicate that law enforcement is suboptimal due to low legal awareness and high tolerance among the population. From an Islamic legal perspective, the regulation of angkringan must be based on the principles of maslaha (common good), adl (justice), ta'awun (social cooperation), and tanzim (organization). A humanistic and solution-oriented approach, such as establishing orderly Angkringan zones and providing Islamically grounded legal education, offers a strategic alternative for ensuring the continued existence of Angkringan without disrupting public order.